STRUKTUR GEOLOGI BAWAH PERMUKAAN DAERAH PEKALONGAN DAN SEKITARNYA BERDASARKAN ANALISIS ANOMALI GAYA BERAT DAN MAGNET - D A Nainggolan (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The result of gravity measurement in the studied area, which is mainly covered by volcanic rocks, has an anomaly value ranging from -11 to 45 mgal. Quantitative interpretation of Bouguer anomaly and magnet shows a subsurface profile depicting the geological processes and tectonic activities. The qualitative analysis results of residual and Bouguer anomalies indicate faults mainly have east - west and north - south directions. Meanwhile, the quantitative analyses of three subsurface model profiles show the graben structure in the Subah area to the south east of Batang city. Â Keywords : gravity, magnet, faults, graben, structural geology, Pekalongan area